The Impact of Environmental Pollution on Ethnic Unrest in Xinjiang: A Uyghur Perspective. (September 2019) - Baranovitch, Nimrod
Since the early 1990s, the Xinjiang Uyghur Autonomous Region has been one of the most restive areas in China, and in recent years, following the July 2009 Urumchi riots, it has experienced frequent incidents of severe ethnic violence. A large body of scholarship has attempted to explain the sources of Uyghur discontent and pointed to various factors, including cultural and religious repression, unemployment, discrimination, and the mass migration of Han Chinese settlers into the region. This article proposes that environmental degradation, a factor that so far has received little attention in the research that focuses on ethnic tension in Xinjiang, is another important contributing factor. Focusing on air and water pollution in Xinjiang, but also addressing other types of environmental degradation, the article examines the attitudes of Uyghurs toward the phenomenon and shows how their perceptions have affected and been affected by their tense relationship with the Chinese government and the Han Chinese settlers in the region.